Online Purchase Intention of E-Commerce Consumers West Java: Application of the Extended Technology Acceptance Model - Akbar, Ilham; Manalu, Vigory Gloriman (Enrichment : Journal of Management, 2023)
The aimed of this research is to determine the effect Perceived usefulness dan perceived ease of use on online buying interest in the West Java region. This study uses a quantitative exploration strategy through the use of surveys. The population of this research is internet users who come from West Java, Indonesia. The sampling technique used in this study namely purposive sampling. Overall, there were 190 questionnaires distributed, and 178 (93.7%) questionnaires that could be used for statistical testing. The statistical analysis technique used in this study is the regression test using STATA. This research found perceived usefulness and perceived ease of use can affect online purchase intention. The contribution that can be made from this research is that perceived usefulness has the biggest impact on online purchase intention